2008
DOI: 10.1111/j.1748-0361.2008.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural Residence and Prescription Medication Use by Community‐Dwelling Older Adults: A Review of the Literature

Abstract: Geographic location may not be as important a variable for medication usage as for other health services utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
8
0
4
Order By: Relevance
“…Não foram localizados estudos comparando diferenças na prevalência de polifarmácia entre idosos moradores na área urbana e rural. Em uma revisão de estudos que avaliaram a intensidade de uso, os achados de pesquisas realizadas na Finlândia e nos estados da Pensilvânia e Carolina do Norte, nos Estados Unidos, foram inconsistentes 11 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Não foram localizados estudos comparando diferenças na prevalência de polifarmácia entre idosos moradores na área urbana e rural. Em uma revisão de estudos que avaliaram a intensidade de uso, os achados de pesquisas realizadas na Finlândia e nos estados da Pensilvânia e Carolina do Norte, nos Estados Unidos, foram inconsistentes 11 .…”
Section: Discussionunclassified
“…Poucos estudos têm investigado diferenças em relação ao padrão de acesso e utilização de serviços de saúde entre populações rurais e urbanas, incluindo acesso a medicamentos 11,24 . No 25 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Previous studies examined the relationship between urban/rural dwelling adults and the use of prescription medications (Carrie et al, 2006;Grymonpre & Hawranik, 2008). These studies found location of residence did not have an effect on prescription drug purchase and use (Carrie et al, 2006;Grymonpre & Hawranik, 2008).…”
Section: Geographical Locationmentioning
confidence: 99%
“…To date there are a handful of studies examining the connection between geographic location (rural versus urban) and prescription medication use (Carrie et al, 2006;Grymonpre & Hawranik, 2008). However, there is a dearth of studies examining the relationship between an individual's geographic location as a risk for stockpiling medications in the home.…”
Section: Drug Costsmentioning
confidence: 99%